Daily Activity of Southern Cassowary (Casuarius casuarius Linnaeus, 1758) in Bali Zoo, Gianyar - Purbaya, Alia Ambara Putri; Yuni, Luh Putu Eswaryanti Kusuma; Sudaryanto, Fransiscus Xaverius (Metamorfosa: Journal of Biological Sciences, 2022)
The Southern Cassowary (Casuarius casuarius Linnaeus, 1758) is an endemic species whose presence has a major influence on forest ecology in Papua. As a frugivore, this bird plays a role in spreading the seeds of fruit trees which make up 90% of tree species in Papua's forests. However, the population of this bird in its natural habitat has decreased due to forest conversion as the population grows, and is exacerbated by hunting by the local community. Ex-situ conservation is carried out with the aim of breeding animals outside their natural habitat, so research on the daily activities of the Southern cassowary is required. This study was conducted from January 10 to February 21, 2022 on five individual Southern Cassowaries at the Bali Zoo. The method used was focal animal sampling with instantaneous recording for 30 minutes with one-minute intervals. The data obtained were tabulated and analyzed using Microsoft Excel, then described descriptively. The most common activity for the Southern Cassowary at Bali Zoo was resting (35.69%), followed by moving activities (19.69%), foraging (18.58%), preening (16.74%), alert (6.69%), vocalization (1.19%), defecation (0.48%), and urination (0.14%). This study shows that the Southern Cassowary can reflect its daily activities naturally while at the Bali Zoo conservation institution which indicates that animal welfare is fulfilled. Keyword : meloxicam, moringa oleifera , sperm quality, testosterone hormone